2021
DOI: 10.3390/cancers13164211
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oral Cancerogenesis Is Impaired in PI3Kγ Knockout and Kinase-Dead Mice

Abstract: We investigated the role of PI3Kγ in oral carcinogenesis by using a murine model of oral squamous carcinoma generated by exposure to 4-nitroquinoline 1-oxide (4NQO) and the continuous human cancer cell line HSC-2 and Cal-27. PI3Kγ knockout (not expressing PI3Kγ), PI3Kγ kinase-dead (carrying a mutation in the PI3Kγ gene causing loss of kinase activity) and wild-type (WT) C57Bl/6 mice were administered 4NQO via drinking water to induce oral carcinomas. At sacrifice, lesions were histologically examined and stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…41 42 Our data using a pharmacological inhibitor of PI3Kγ are consistent with a recent report that observed reduced rates of preneoplastic lesions and SCCs induced by 4NQO in the tongues of genetically engineered mice lacking PI3Kγ or expressing a kinase-dead PI3Kγ compared with wild-type C57Bl/6 mice. 43 In addition to reducing progression of dysplasia and preventing tumorigenesis, we also demonstrated that inhibition of PI3Kγ reduces Ly6G+ cell recruitment to sites of dysplasia and that these leukocytes play a critical role in establishing invasive SCC. While studies using PI3Kγ inhibitors have acknowledged an influence on PMN-MDSCs, these studies largely focus on tumor-associated macrophage polarization and activity or a more general effect on tumorassociated myeloid cells broadly.…”
Section: Discussionmentioning
confidence: 59%
“…41 42 Our data using a pharmacological inhibitor of PI3Kγ are consistent with a recent report that observed reduced rates of preneoplastic lesions and SCCs induced by 4NQO in the tongues of genetically engineered mice lacking PI3Kγ or expressing a kinase-dead PI3Kγ compared with wild-type C57Bl/6 mice. 43 In addition to reducing progression of dysplasia and preventing tumorigenesis, we also demonstrated that inhibition of PI3Kγ reduces Ly6G+ cell recruitment to sites of dysplasia and that these leukocytes play a critical role in establishing invasive SCC. While studies using PI3Kγ inhibitors have acknowledged an influence on PMN-MDSCs, these studies largely focus on tumor-associated macrophage polarization and activity or a more general effect on tumorassociated myeloid cells broadly.…”
Section: Discussionmentioning
confidence: 59%
“…Total proteins from each saliva sample (30 µg) were separated by SDS-PAGE as previously reported [ 56 ]. Gels were transferred to membranes, saturated with blocking solution (5% milk and 0.1% Tween-20 in PBS), and incubated with anti-CST1 primary antibody (1:500; Santa Cruz Biotechnology Inc., Dallas, TX, USA) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Total proteins from each saliva sample (30 µg) were separated by SDS-PAGE as previously reported [56]. Gels were transferred to membranes, saturated with blocking solution (5% milk and 0.1% Tween-20 in PBS), and incubated with anti-CST1 primary antibody (1:500; Santa Cruz Biotechnology Inc., Dallas, TX, USA) overnight at 4 • C. Membranes were then rinsed three times and incubated with the appropriate concentration of secondary antibody conjugated with horseradish peroxidase for 1 h at room temperature.…”
Section: Western Blotmentioning
confidence: 99%
“…The sections were dehydrated with ascending ethanol passages and mounted in dibutylphthalate polystyrene xylene (DPX), (BDH) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%